If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(5a + 5) + -3(a + -6) = 0 Reorder the terms: -1(5 + 5a) + -3(a + -6) = 0 (5 * -1 + 5a * -1) + -3(a + -6) = 0 (-5 + -5a) + -3(a + -6) = 0 Reorder the terms: -5 + -5a + -3(-6 + a) = 0 -5 + -5a + (-6 * -3 + a * -3) = 0 -5 + -5a + (18 + -3a) = 0 Reorder the terms: -5 + 18 + -5a + -3a = 0 Combine like terms: -5 + 18 = 13 13 + -5a + -3a = 0 Combine like terms: -5a + -3a = -8a 13 + -8a = 0 Solving 13 + -8a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -8a = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -8a = 0 + -13 -8a = 0 + -13 Combine like terms: 0 + -13 = -13 -8a = -13 Divide each side by '-8'. a = 1.625 Simplifying a = 1.625
| 48+6x=90 | | 5e^1+7=12 | | 9x+1=3x-13 | | 2x+6.8+8x+1.4+x=90 | | 3s^2-26s-9= | | 8p+7=13+7p | | -2(1-4x)=6x+12 | | 7(7x-1)-18=47x+7 | | 8b=2b | | 64c^2-16=0 | | 5(2x-4)=0 | | -8(x+3)+2x+5=7x+9 | | 3+x+27=180 | | (2x+3)(4x-4)= | | [9(p+4)-18]-[2(p-4)+1]= | | 9(2k+3)+2=11(k-.5) | | .4x+7=.6x | | 2c-7=18 | | .8x-.2y-.1x-1.2y=.7 | | y-3/3-y-2/2=-1 | | 18/65=x/35 | | 9(q+9)= | | 13(4x+4)=3(5x+6) | | 5x=23+y | | 100(29)=10(29) | | 2xsquared-x=3 | | Y/9-6=-14 | | 5x+9=9+2x | | 8x-11/7=-5 | | z/15-6=14 | | 3x-12=-4x+32 | | v=(p*q)-((p*q)/100*5)-p |